Tradisi Membaca Ayat-Ayat Alquran Sebelum Belajar (Studi Living Quran di MAN Kota Batu) - Baity, Muhammad Yusuf; Nidhom, Muhammad (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2022)
MAN Batu City is an Islamic school under the auspices of the Ministry of Religion. The problem raised in this research is related to how the procession goes on, and how the people of MAN Kota Batu interpret it. Therefore, the main point of this research is to find out the traditional procession of reciting selected verses before learning and to find the meaning hidden behind this tradition. This research is a research using descriptive method with the Living Qur'an research model whose focus of study lies in the aspect of the use and implementation of the Qur'an in everyday life. Through this research, it is hoped that it can increase the awareness of MAN Batu City residents and readers to always interact with the Koran. Based on the results of the research, it was found that the procession of the tradition of reciting selected verses before learning at MAN in Batu City begins with the recitation of al-Fâtihah, followed by two sentences of creed. Followed by reading Surah al-Baqarah verse 32, Surah Thâhâ verses 25-28 and excerpts from Surah Thâhâ verse 114 which are accompanied by hadiths. In interpreting this tradition, the majority of MAN Batu City residents consider tradition as a form of hope and a request to Allah SWT to be given convenience in all matters, especially in terms of studying.